Developing Walking Methods for Lifecourse Research - Aled Singleton (Linking Ages: A Dialogue between Childhood and Ageing Research, 2024)
This chapter presents and analyses empirical case studies from the United Kingdom, where three different walking methods uncover memories and emotions connected to earlier stages of the lifecourse. Alongside conventional outdoor walks, this writing describes both an oral method and an online digital approach that help the individual to imagine their walking body passing through spaces such as the house, street, and neighbourhood. These three connected methodologies change the format of biographical accounts from chronological to geographical, and so reveal rich accounts concerning topics such as homelife, leisure, and mobilities. Moreover, this approach helps to understand others' social and economic contexts, particularly when biographies are (re)presented for wider consumption on curated public walks and through an artistic film project. This chapter offers ways for researchers of different chronological ages and backgrounds to the interviewees find common ground, thus offering Linking Ages methodologies to understand the relationships that contemporary children have with space and place.